Development of Business Intelligence in a Cargo Company Using the Agile Scrum Approach - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This research uses the Agile Scrum approach to develop Business Intelligence (BI) in a cargo company. The problems faced in the cargo industry, such as fuel price volatility and demand fluctuations, demand an adaptive and fast BI solution. The method includes stages from requirements definition to testing with Agile Scrum as the main framework. The results showed that developing BI with this approach resulted in a more adaptive, rapid, and high-quality solution. The contribution of this research is to provide a better understanding of the use of Agile Scrum in the context of BI development, provide practical guidance for the cargo industry, and provide empirical evidence of the effectiveness of this methodology in improving the efficiency and effectiveness of BI development.